Penerapan Metode Analytical Hierarchy Process (AHP) dalam Mengoptimalkan Alokasi Dana Desa di Desa Catur Karya Kecamatan Haruai Kabupaten Tabalong - Herawati; Ahmad Yunani (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2026)
This research is motivated by the importance of optimizing Village Fund allocations as a fiscal instrument to foster local economic independence and community welfare in Catur Karya Village, Tabalong Regency. The primary focus of this study is to determine the priority scale of Village Fund utilization to address the challenges of budget constraints amidst the highly dynamic needs of village development. The methodology applied is a qualitative descriptive approach using the Analytical Hierarchy Process (AHP) instrument. The analysis results show that three main criteria serve as the basis for consideration: alignment with the Village Mid-Term Development Plan (RPJMDesa), village potential strengths, and urgent problems. Based on the weight calculations, the priority order for village expenditure allocation was found as follows: community empowerment sector (43%), village development (29%), community guidance (17%), and village government administration (11%). The study concludes that community empowerment is the most dominant component that must be prioritized to create inclusive economic growth.